Parent Module in the Handayani University Makassar Information System Website using Laravel Framework - Rumonang, Datu; Anatasya, A Edet Fauri; Wahyuni, Eka Dyar (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2025)
This study aims to develop a web-based academic information system at Handayani University Makassar that enables parents to directly monitor their children's academic progress. The system addresses previous limitations, where academic information was only accessible to students, thereby reducing parental involvement. This system includes features that enhance transparency and communication effectiveness between the university and parents, such as access to Study Plan Cards (KRS), automated notifications, and payment status monitoring. The system was developed using the waterfall method, which includes the stages of analysis, design, coding, and testing. The Laravel framework was chosen for its Model-View-Controller (MVC) architecture, data security, and ease of management. As a web-based system, it can be accessed anytime and anywhere via internet-connected devices. The results indicate that the system successfully supports students’ academic success by improving transparency, parental engagement, and communication with the university. With its comprehensive features and user-friendly design, the system offers an innovative solution that promotes a more inclusive and informative academic environment in the digital era.